(untitled) (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2021)
This effort was performed to investigate the linear and nonlinear optical (NLO) properties of two 1,2,3-triazole derivatives in several solvent media and in gas-phase at PCM/DFT/CAM-B3LYP/6-311+G(d) level of theory. The static and dynamic NLO parameters as the total dipole moment, the average linear polarizability, the Hyper-Rayleigh Scattering (HRS) first hyperpolarizability, and the average second hyperpolarizabilityare calculated as function of static dielectric constant of the solvents. The computational linear and nonlinear optical studies revealed that both the triazoles derivatives are promising materials for NLO applications.